The Impact of a New Accounting Standard on Assets, Liabilities and Leverage of Companies: Evidence from Energy Industry - Ireneusz Górowski; Bartosz Kurek; Marek Szarucki (Energies, 2022)
The climate policy of the EU enforced substantial changes for producers and suppliers of energy. New assets and providers of capital are needed to fulfill the policy requirements. To provide comparability and facilitate an investment process, EU law requires companies to prepare annual financial statements according to International Financial Reporting Standards. One of these accounting standards—IFRS 16 Leases—specifies how to recognize, measure, present and disclose leases. It came into force in 2019 and implemented a single lessee accounting model, contrary to a dual accounting approach for lease accounting. The latter approach enabled companies to keep leased tangible assets and respective liabilities off-balance sheet. By using a sample of companies from the energy industry (oil, gas, energy and mining sectors) that are listed on the Warsaw Stock Exchange, we examine, measure, and analyze the impact of IFRS 16 Leases implementation on the value of assets, liabilities and leverage on assets and leverage on equity. The paper may serve as an insightful case study of how the implementation of a new standard influences the financial situation of the affected companies in the energy industry. Our paper contributes to the scientific debate in the following three ways: (1) we confirmed the influence of IFRS 16 Leases on assets, liabilities, leverage on assets and leverage on equity that was anticipated in the literature, (2) using the auditing methodology, we demonstrated the material changes of assets and liabilities in the energy industry, (3) based on the research results, we suggested recommendations for further scientific studies.